Cases in international relations : pathways to conflict and cooperation - Hastedt, Glenn P., 1950- (Los Angeles : SAGE/CQ Press, 2015)
This text helps students understand the context of headline events in the international arena. Organized into three main parts - military, economic, and human security - the book's fifteen cases examine enduring and emerging issues from the longstanding Arab-Israeli conflict to the rapidly changing field of cyber-security. Compatible with a variety of theoretical perspectives, the cases consider a dispute's origins, issue development, and resolution so that readers see the underlying dynamics of state behavior and can try their hand at applying theory.
1. Pathways to conflict and cooperation -- 2. Power management in the South China Sea -- 3. Interstate war with Iraq -- 4. The cyclical Arab-Israeli conflict -- 5. Iran's nuclear ambitions -- 6. Responding to terrorism after 9/11 -- 7. Cybersecurity's uncertain battleground -- 8. Organizing world trade -- 9. Food aid as a solution to world hunger -- 10. Global monetary reform after 2008 -- 11. Uniting Europe through a common currency -- 12. Humanitarian relief after Haiti's earthquake -- 13. Libya's uprising and the responsibility to protect -- 14. Governing the global commons of the Arctic -- 15. Immigration tensions over the U.S.-Mexico border -- 16. Social responsibility and the BP oil spill.
Includes bibliographical references and index.
Keywords: International relations -- Case studies; Peace-building -- Case studies; Conflict management -- Case studies